Association of colistin residues and manure treatment with the abundance of mcr-1 gene in swine feedlots. (June 2019) - Xia, Xi; Wang, Zheng; Fu, Yulin; Du, Xiang-dang; Gao, Binwen; Zhou, Yuqing; He, Junjia; Wang, Yang; Shen, Jianzhong; Jiang, Haiyang; Wu, Yongning
Abstract: Background: The extensive use of colistin in swine production may have contributed to the recent emergence of corresponding mobile resistance gene mcr - 1 . The use of colistin as a feed additive was banned in China in April 2017. Objectives: To examine the occurrence of colistin and dissemination of mcr - 1 in swine feedlots before and after the colistin ban and effects of different manure treatments. Methods: Environmental samples were collected from swine feedlots before (December 2016) and after (December 2017) the colistin ban. Colistin concentrations were determined by ultra-high performance liquid chromatography coupled to tandem mass spectrometry. The prevalence of mcr - 1 were determined by quantitative PCR analysis, while bacterial community composition was investigated by 16S rRNA sequencing. Results: In 2016, colistin was detected in feed and fresh manure samples at 67 mg/kg and 17 mg/kg, respectively, but was absent from all samples in 2017. In 2016, the relative abundance of mcr - 1 in fresh manure was lower than that in solid samples after natural drying, while a higher relative abundance was detected in fresh manure samples compared with biogas slurry samples. A strong correlation between colistin concentration and relative abundance of mcr - 1 was observed in fresh manure. The samples collected in 2017 showed a lower relative abundance of mcr - 1 compared with those collected in 2016. Bacterial community analysis showed that the abundance of Enterobacteriaceae, which act as a vehicle and reservoir of mcr - 1, increased with natural dying but decreased with anaerobic digestion. Conclusions: The presence of colistin exerts direct selection pressure for the accumulation of mcr - 1 in manure, while the ban on colistin likely halted the dissemination of mcr - 1 on pig farms. Anaerobic digestion is an effective waste treatment process for removing mcr - 1, which might be mainly driven by the shift in bacterial community structure. Highlights: The presence of colistin exerts direct selection pressure for the accumulation of mcr-1 in swine feedlots. The ban on the use of colistin as an animal feed additive helped decrease the prevalence of mcr-1 in pig farm environments. Anaerobic digestion is an effective waste treatment process for removing mcr-1 .